Afterword on Islam and space in Europe: the dynamism of a field. Issue 10 (9th August 2021) - Knott, Kim
ABSTRACT: This Afterword focuses on the dynamism of the study of Islam and space in Europe. A comparison with Barbara Daly Metcalf's Making Muslim Space in North America and Europe (1996) reveals how much has changed in terms of scholarly approach since its publication. In Metcalf's volume, the frames were migration, mobility and transnational connections. Here, urban diversity, settlement, and secularism are highlighted. Despite a common anthropological focus, today's authors pay greater attention to theoretical issues, drawing on ideas about space, governance and the everyday to deepen their ethnographies and engage across disciplines. They have the advantage of being able to examine the impact of time and change. Three final questions are raised, on the move from global to local, the role of academic research in societal problem solving, and the study of Islam as a resource for interrogating the "secular" public domain and everyday lived space in Europe.